Un biombo de Ovidio: estudio material, iconográfico y cultural - Baena Zapatero, Alberto; Jiménez García, José Ángel (2022)
Estudio de un biombo inédito del último tercio del siglo XVII o inicios del siglo XVIII. A partir de un estudio técnico e iconográfico que revele la historia de la propia pieza se relacionarán los resultados con el tema elegido por el pintor y el contexto sociocultural de la época. Se identifican los grabados en los que se inspiró el pintor y se relacionan con la circulación de la obra de Ovidio en América, el contexto suntuario de un biombo de esas características o el tránsito de libros y saberes desde el viejo continente.
This research aims to study an unknown folding screen dated in the last third of the 17th century or early 18th century. Based on a technical and iconographic study that reveals the history of the piece itself, the results will be linked to the theme chosen by the painter and the socio-cultural context of his time. The engravings that inspired the painter are identified and related to, among other issues, the circulation of Ovid’s work in America, the sumptuary context of a screen of these characteristics, or the arrival of books and knowledge from Europe.
Keywords: Ovidio Nasón, Publio; Iconografía; Cultura